1990
DOI: 10.1111/j.1469-7610.1990.tb00803.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Characteristics of Children who Suffer from Headache: A Research Note

Abstract: Twenty-three volunteer subjects were compared with 23 (matched) control subjects on self and parental ratings of anxiety, depression, shyness-sensitivity, sleeping difficulties, perfectionism, psychosomatic problems (unrelated to headache), other behavioural disturbances, major life stress events and parental expectations (i.e. achievement orientation). Results indicated that the headache children showed significantly higher shyness-sensitivity, psychosomatic problems and behavioural disturbances and significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
54
5
3

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(69 citation statements)
references
References 36 publications
7
54
5
3
Order By: Relevance
“…Often this can be a source of conflict, anxiety and mood problems-factors known to be associated with headache. 28 In conclusion, the prevalence of headache and migraine among schoolchildren in this country are similar to other parts of the world, but there may be culturally set factors that play a role in determining the extent of these phenomena. Consanguineous marriages, social expectations, social restrictions and role models (particularly in relation to somatization), seem to be prime candidates.…”
Section: Discussionmentioning
confidence: 86%
“…Often this can be a source of conflict, anxiety and mood problems-factors known to be associated with headache. 28 In conclusion, the prevalence of headache and migraine among schoolchildren in this country are similar to other parts of the world, but there may be culturally set factors that play a role in determining the extent of these phenomena. Consanguineous marriages, social expectations, social restrictions and role models (particularly in relation to somatization), seem to be prime candidates.…”
Section: Discussionmentioning
confidence: 86%
“…Several studies have reported that children and adolescents with headache show greater indices of psychopathology [Bille, 1962;Maratos and Wilkinson, 1982;Lanzi et al, 1983;Larsson, 1988;Kowal and Pritchard, 1990;Guidetti et al, 1998]. Also, this population shows a higher risk of developing psychological disorders in adulthood than occurs among healthy controls [Fearon and Hotopf, 2001].…”
Section: Nonpharmacological Prophylactic Treatmentmentioning
confidence: 96%
“…Family problems and disturbed family relationships may be more common in families with children with severe headache or psychiatric comorbidity [42]. Anxiety and depression in the parents of juvenile headache sufferers have been investigated in small samples only, giving conflicting conclusions [43].…”
Section: Discussionmentioning
confidence: 99%